Song of the sea [videorecording (Blu-Ray + DVD)] - Collins, William (Screenwriter); Rawle, David; Gleeson, Brendan; Hannigan, Lisa; Flanagan, Fionnula, 1941-; O'Connell, Lucy; Kenny, Jon; Shortt, Pat; Ó Snodaigh, Colm; Hourican, Liam; Swierszcz, Kevin; Coulais, Bruno (Universal Studios Home Entertainment, 2015)
Saoirse and her brother Ben encounter a host of ancient and mythical characters on their journey to preserve the spirit world, awaken Saoirse's own magical powers, and discover secrets of their family's past.